Zebrafish and water microbiome recovery after oxytetracycline exposure. (1st March 2021) - Almeida, Ana Rita; Domingues, Inês; Henriques, Isabel
Abstract: Oxytetracycline (OTC) is a broad-spectrum antibiotic widely used in aquaculture, resulting in contamination of aquatic environments. In a previous study, we observed significant effects of OTC sublethal concentrations in zebrafish, its microbiome and the water bacterial community. Here we assessed the extent to which these effects are reversible after a recovery period. Zebrafish adults were exposed to OTC (10, 000 μg/L) via water exposure. Effects were analyzed at 5 days (5 dE) and 2 months (2 mE) of exposure and recovery was assessed at 5 days (5dPE) and 1 month (1mPE) after exposure Impacts were observed in fish energetic reserves and in fish and water microbiomes structure, being significant even at 5 dE. At energetic reserves level, the effect in cellular energy allocation (CEA) was dependent on the exposure time: initially CEA increased while after 2 mE CEA decreased. At microbiome level, diversity was not affected but the richness of the water microbiome significantly decreased at 2 mE. Regarding the post-exposure period, at CEA level, organisms seem to recover. In water and gut microbiomes OTC effects were also attenuated after exposure ceases, indicating a recovery. Even so, the structure of water exposed community remained significantly different towards the control, while richness of this community significantly increased at 1mPE. During exposure the relative abundance of 11 and 16 genera was significantly affected in the gut and water microbiomes, respectively, though these numbers decreased to 4 and 8 genera in the post-exposure period. At functional level during exposure 12 and 13 pathways were predicted to be affected in zebrafish gut and water microbiomes respectively, while post-exposure few pathways remained significantly affected. Hence, our results suggest a recovery of the fish fitness as well as of the water and intestine microbiomes after exposure ceases. Even so, some of the effects caused by OTC remain significant after this recovery period. Graphical abstract: Image 1 Highlights: Zebrafish adults were exposed to OTC for 2 months and allowed to recover for 1 month. OTC effects were observed after 5 days and 2 months of exposure. After a post-exposure period, fish recovered at energetic reserves level. Zebrafish gut microbiome also recovered at structural and functional levels. Water microbiome also recovered but OTC effects were still significant after 1 month. Abstract : Oxytetracycline impacts both fish energetic reserves and fish gut and water microbiome. After exposure ceased, a re-adjust of fish fitness and water microbiome occurs.